Case Report: Safe and Effective Sublingual Birch Allergen Immunotherapy in Two HIV-Positive Patients - Latysheva, Elena; Nazarova, Evgeniya; Latysheva, Tatiana; Ilina, Natalia (Frontiers in Immunology, 2021)
Allergen-specific immunotherapy (AIT) is a safe, effective treatment for respiratory allergies (such as moderate-to-severe allergic rhinoconjunctivitis) that are not controlled by symptomatic medications. The indications and contraindications for AIT have been defined in international guidelines and consensus statements. However, some of these contraindications are not evidenced- based but have been deduced from the theoretical risk of an interaction between AIT disease-modifying effect and immune or inflammatory comorbidities. In the absence of clinical trial evidence, the accumulation of experience as case reports can narrow the spectrum of absolute contraindications. The majority of international guidelines list HIV infection as a contraindication to AIT. Here, we describe two cases of safe, effective sublingual birch pollen AIT in HIV-positive patients undergoing concomitant antiretroviral therapy. A 32-year-old female and a 63-year-old male sensitized to tree pollen and with clinically confirmed birch pollen allergy underwent pre- and co-seasonal sublingual birch pollen AIT for three and two pollen seasons, respectively. The therapy was associated with a marked reduction in the frequency and intensity of allergic symptoms, and the reduced use of (symptomatic) rescue medication. Mild, local, treatment-emergent adverse events were noted throughout the course of treatment but resolved spontaneously. No serious adverse events were reported. In particular, there were no obvious harmful effects on the patients’ immune status or viral load. Hence, sublingual birch pollen AIT proved to be effective and safe in two HIV-positive patients.